RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND ADOLESCENT ATTITUDES TOWARDS FAST FOOD CONSUMPTION BEHAVIOR OF CLASS (X) STUDENTS AT TAMAN SISWA HIGH SCHOOL (TAMSIS) PEMATANGSIANTAR - Sondang Sidabutar (RADJA PUBLIKA, 2023)
This study aims to determine: (1) the level of knowledge of class (x) students at Taman Siswa high school (Tamsi) Pematangsiantar about fast food consumption. (2) The attitude of class (x) students at Taman Siswa high school (Tamsis) Pematangsiantar regarding fast food consumption. (3) The behavior of class (x) students at Taman Siswa high school (Tamsis) Pematangsiantar regarding fast food consumption. This type of research is a survey type research. This research was conducted from July to September 2019. The population in this study were high school students in class (x) at Taman Siswa High School (Tamsis) Pematangsiantar with a total of 303 students. The data collection technique uses the product moment correlation formula and reliability uses the Cronhbach alpha formula and involves 75 class (x) students at Taman Siswa Pematangsiantar High School as a response to the research instrument trial. The analysis technique uses descriptive analysis. The results of this study were: (1) The level of knowledge of class (x) students at SMA Taman Siswa (Tamsis) Pematangsiantar regarding the consumption of fast food (fast food) in the good category was 46 people (61.3%), in the less good category there were 29 people (38.7%). (2) Attitudes of class (x) students at Taman Siswa High School (Tamsis) Pematangsiantar regarding the consumption of fast food in the agree category as many as 55 people (73.3%) in the disagree category as many as 20 people (26.7%) .